Undifferentiated Embryonal Sarcoma of the Liver Involving All Major Hepatic Veins Treated by Left Extended Trisectionectomy - Reinaldo Fernandes; Klaus Steinbrück; Jan-Peter Périssé; Rodrigo Luz; Renato Cano; Fernanda Cruz-Nunes; Diego Garcia; Rodrigo Diaz; Fernanda Cavalcanti Carneiro; Andrea Velloso; Carlos Frederico Campos; Marcelo Enne (Case Reports in Surgery)
Introduction. Over the past few years, liver surgery has been in constant evolution and gained many improvements that helped surgeons push limits further. A complex procedure such as left extended trisectionectomy, as described by Makuuchi in 1987, may be performed in selected cases. Aim. Describe a case of successful resection of a huge bilobar liver sarcoma involving all hepatic veins from a young female patient, in which the blood outflow was preserved through an inferior right hepatic vein, leaving only segment 6 as liver remnant. Case Report. A 19-year-old female with a 3-month history of abdominal pain, vomiting, and weight loss was referred for our evaluation. CT scan and MRI revealed a heterogeneous and bulky expansive hepatic lesion, sparing only segment 6, with an estimated volume of 530 cm3, corresponding to a 1.2 FLR/BW ratio. The tumor involved the three major hepatic veins, but an inferior right hepatic vein was present, draining the spared segment 6. She was submitted to a left trisectionectomy extended to the caudate lobe and segment 7, including resection of all hepatic veins and lymphadenectomy of the hepatic pedicle. She was discharged on the 7th postoperative day without complications. The histopathological and immunohistochemical analysis demonstrated an undifferentiated embryonal sarcoma of the liver. Conclusion. Inferior right hepatic vein-preserving left extended trisectionectomy is a safe and feasible procedure that should be performed by a hepatobiliary team experienced in major complex hepatectomies.